TRACKING CONTROL OF QUANTUM VON NEUMANN ENTROPY - XING, YIFAN (International Journal of Psychosocial Rehabilitation, 2020)
This paper provides the accurate tracking control of the von-Neumann entropy of quantum systems. The closed form of the accurate time derivative of the entropy is presented. Based on this, controller design method for time-dependent decay rate is provided, which can directly drive the entropy to track a desired trajectory. Simulations are done on two-level quantum system.